METODE DISKUSI MENINGKATKAN BELAJAR FAKTORISASI PRIMA UNTUK MENENTUKAN KPK DAN FPB - Tuminah Tuminah (JURNAL PENDIDIKAN ROKANIA, 2017)
Discussion method can to improve mastery of students about the use of prime factors to determine KPK and FPB for class IV SD Negeri 006 Rambah Kabupaten Rokan Hulu” Using this method writer is very consider the time the state of the students, and inditification of the problem before to do classroom action research, so precisely taking action poved to be a successive increase from cycle I meeting I until cycle II meeting II evident in the cycle. This method can to do with identification of the problem, formulate of the problem, planning and carry out the action, and evaluated so that the result achieved cam improve student achievement